Transcription Factor: A Powerful Tool to Regulate Biosynthesis of Active Ingredients in Salvia miltiorrhiza - Wu, Sijia; Zhu, Bo; Qin, Luping; Rahman, Khalid; Zhang, Lei; Han, Ting (Frontiers in Plant Science, 2021)
Salvia miltiorrhiza Bunge. is one of the most widely used herbs in traditional Chinese medicine. And the major active ingredients of S. miltiorrhiza, phenolic acids and tanshinones, are useful to treat vascular diseases. Due to their great pharmaceuitical activity and low quality in wild S. miltiorrhiza plants, researches focused on enhancing the phenolic acids and tanshinones yield in plants became a hotspot. Transcription factors, which activate or inhibit the multiple genes involved in one or more biosynthetic pathways, are powerful tools for controlling gene expression in biosynthesis. Several families of transcription factors have been reported to participate in regulating the biosynthesis and accumulation of phenolic acids and tanshinones. This review summarizes the investigations in these fields, with focus on identified transcription factors in recent years and their functions in phenolic acid and tanshinone biosynthesis regulation, and provide new insight for further research. Finally, the application of the biosynthetic regulation of active ingredients by transcription factors in S. miltiorrhiza are discussed.